The use of the legend of sleepy hollow in EFL classrooms - Diniz, Gabriely Cristina Queiroga (Open Science Journal, 2020)
Considering the value of literary texts as authentic language materials to provide real uses of lexical and syntactic items and interesting subjects for students to connect better with the language. In addition, taking in account the characteristic of light horror presented by Irving in the story proves adaptable for different levels and ages, we should use this factor to attract the student for the subjects of our planning. As the use of literature in language lessons stimulates mostly the use of three skills: reading, writing and speaking. This short article collects activities prepared to help EFL students to advance in these areas, and, by the addition of the video as a resource, which presents a context of leisure and entertainment, and could modify student’s posture and expectations in relation to its use (MORÁN, 1995).